Pendidikan Politik di Partai Politik yang Impoten: Kajian Kritis Fenomena Calon Tunggal pada Pilkada - Aba, Akbar; Matang, Matang; Suryadi, Karim (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2023)
The single candidate for regional elections continues to increase. This study aims to describe the factors that cause the occurrence of a single candidate, theories and models that can explain this phenomenon, and the position of democracy in the election of a single candidate. Using Harzing's Publish or Perish software, 195 articles were obtained from 2013-2022. Through the Systematic Literature Review method, 50 journal articles were then analyzed. The results of the study explain that political education in political parties fails to cause a single candidate. Pragmatism of political parties, high political dowries, and failure of regeneration. Finally, make political parties form a grand coalition with a single candidate. Several theories can explain this phenomenon, such as Coalition Theory, Exchange Theory, Interest Groups Theory, Oligarchy Theory, Hegemony Theory, Deliberative Democracy, and others. In the study of democracy, a single candidate ultimately has an impact on the quality of democracy. This research opens up space for further research discussed in this article.